Effects of integrating a mobile game-based learning framework in a cultural tourism setting - Pathathai Na Lumpoon (2018)
© 2016 IEEE. Cultural activities such as visiting museums, galleries, and historical sites have received a large amount of attention from tourists and researchers. Many existing research studies have integrated location-based technologies as tools to support the visiting of historical and cultural sites. However, young visitors tend to be puzzled or bored as the above-mentioned technology systems attempt to automatically provide annotation content based only on the current positions of the visitors. In this paper, we have proposed a mobile game-based tourism system called the Walk Rally application that would reduce the gap that presently exists among youths with regard to learning about culture. The Walk Rally application aims to explore how mobile gaming can help users enhance their experiences of history, culture, arts and languages. We have investigated the satisfaction levels of young tourists and the learning of history that takes place when visiting cultural areas in Chengdu City, China. The experimental results have revealed that the young tourists have expressed a moderate level of satisfaction with the game content.